Efficacy of pulsed radiofrequency treatment on the saphenous nerve in patients with chronic knee pain - (:unkn) unknown (IOS PRESS, 2011)
Background and objective: We studied the long-term efficacy of pulsed radiofrequency treatment (PRF) on the saphenous nerve in 115 patients with chronic knee pain. Materials and methods: 115 patients with chronic knee pain were investigated in a period of 22 months retrospectively. All patients had pulsed radiofrequency to the saphenous nerve. The mean age was 59 (range, 51-67). All patients were accessed with the visual analog scale (VAS) and WOMAC score pain at rest, pain on movement, and pain in flexion at 10th day, 3rd and 6th months post procedure. Results: All patients showed improvement in their VAS scores as well as in their WOMAC scores after ten day, three month, and 6 months (p = 0.001). No side effects were reported. Conclusion: PRF application to the saphenous nerve for eight minutes showed remarkable amount of patient satisfaction. Application of PRF for the second time could be recommended if it shows some benefit after the sixth month. But none of our patients needed a second application of PRF after six months period.
Keywords: Pulsed radiofrequency; saphenous nerve; knee pain; pain relief; peripheral nerve; osteoarthritis; OBTURATOR NERVE; DORSAL-ROOT; OSTEOARTHRITIS; HIP; GANGLION